Evaluation of one-shot vincristine sulfate combined with surgical excision as a new regimen for treatment of canine transmissible venereal tumor - Abouelnasr, Khaled; Hamed, Mohamed A; Eltaysh, Rasha; Elfadl, Eman Abo; Bazeed, Shefaa; Ibrahim, Samah; Fericean, Liana; Farrag, Foad; Salem, Mohamed; Rizk, Awad (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The purpose of this study was to investigate the effectiveness of surgical excision combined with a single shot of vincristine sulfate for treating transmissible venereal tumor (TVT) in dogs. Materials and Methods: Fifty-two dogs were divided randomly into two groups (n = 26). Dogs in Group I were treated surgically by debulking the tumorous mass, whereas dogs in Group II were subjected to a combination of surgery and a single injection of vincristine sulfate. Results: Female dogs showed a high prevalence of TVT compared to males (67.3%, n = 35 vs. 32.7%, n = 17), respectively. The German shepherd’s breed showed a high prevalence of TVT compared to other breeds. There was a positive association between sex and outcomes. Most occurrences of regret in Group II were reported in females (n = 16, 61.5%) compared to male dogs (n = 10, 38.5%). There was also a positive association between breed and outcome. Most occurrences of regret in Group II were reported in German shepherd dogs (n = 16) compared to Group I (n = 7). In Group I, 15 dogs (57.7%) showed a complete regression, and 11 (42.3%) underwent recurrence. However, in Group II, 21 dogs (80.7%) showed a complete regression, and 5 dogs (19.2 %) underwent recurrence. Conclusions: It appears therefore that the simultaneous use of surgery and administration of a single dose of vincristine sulfate could be considered a combination therapy for TVT as it reduces the risk of recurrence and has a reasonable cost. Recognizing potential risk factors associated with TVT in dogs may be helpful in constructing the best preventive measures. J. Adv. Vet. Anim. Res., 11(3): 553–559, September 2024 http://doi.org/10.5455/javar.2024.k805